TiN/PECVD‐Si3N4/TiN diaphragm‐based capacitive‐type MEMS acoustic sensor. Issue 6 (1st March 2016) - Lee, J.; Jeon, J.H.; Kim, Y.‐G.; Lee, S.Q.; Yang, W.S.; Lee, J.S.; Lee, S.‐G.
Abstract : A capacitive‐type MEMS acoustic sensor with a planarised TiN/plasma‐enhanced chemical vapour deposition ‐Si3 N4 /TiN diaphragm based on a polyimide sacrificial layer is presented. The multi‐layer diaphragm has the effective residual stress of +31.5 MPa. Furthermore, this sensor features a 21% lower parasitic capacitance and a 56% lower air‐gap resistance in comparison with those of a sensor fabricated without planarisation. Five photomasks were used. In addition, to evaluate the frequency response, both an effective capacitance model and an equivalent circuit model equipped with a voltage‐controlled voltage source are newly proposed and compared with conventional models. The open‐circuit sensitivity is modelled to −45.4 dBV/Pa at 1 kHz with 9.6 V, indicating a difference of 0.9 dB in comparison with the open‐circuit sensitivity of the conventional model.